FLEXURAL BEHAVIOR OF REINFORCED CONCRETE BEAMS STRENGTHENED WITH HYBRID STEEL- FRP REINFORCEMENTS BY USING NEAR SURFACE MOUNTED TECHNIQUE - Sabah Abdulhameed, Suhaib; Mukheef Hamza, Dina (Journal of Applied Engineering Science, 2023)
This paper investigated the behavior of reinforced concrete (RC) beams of near surface mounted (NSM) strengthening technique with using steel bar and hybrid steel bar. The effects of NSM reinforcement and load patterns on the flexural behavior and ductility of the RC beams have been studied. A four-point bending test was carried out on five reinforced concrete beams divided into two groups. The first group was tested under the effect of static load, whereas the second group was tested under repeated load. The experimental results are reported regarding the failure mode, flexural strength, load-deflection response, cracking behavior, and ductility.  These results showed that strengthening of concrete beams with NSM steel bar increased the yielding and ultimate loads by about 28.6% and 28.5% respectively as compared to control beam, whereas the yielding and ultimate load increased to 33% and 35.7% over the control beam when strengthened with hybrid NSM steel bar. The ductility index of the control beam was equal to 2.6, this value increased to about 24.6% and 52.3% of the NSM steel bar and NSM hybrid steel bar strengthened beams respectively. The repeated load decreased the load capacity of the strengthened hybrid beams by about 65%, whereas the mid-span deflection is nearly the same.
Keywords: near surface mounted technique, hybrid reinforcements, ductility index